“The Development of the Ideas of Scholars of Previous Generations Will Be the Best Monument for Them”: In Memory of Leonid Teodorovich Yablonsky (1950–2016) - Zeleneev Yu.A.; Izmailov I.L.; Nedashkovsky L.F. (Золотоордынское обозрение)
Research objectives: To consider the creative path and main views of L.T. Yablonsky, as well as his influence on ideas about the ethnic history of the Golden Horde population and theoretical problems of ethnogenesis. Research materials: The authors of the article were based on numerous publications by L.T. Yablonsky, as well as personal impressions from meetings with the researcher on expeditions and at academic conferences. Results and novelty of the research: The authors consider the formation of L.T. Yablonsky as a unique specialist who combined archaeological training and professional study of physical anthropology. This allowed him to draw important conclusions about the formation of the Golden Horde population. Later, he resorted to this method to study the early nomads of the Aral Sea region and the South Urals. His works became an event in the research field, since they positively differed from others not only by an interdisciplinary approach to the problem under study – at the junction of archaeology and ethnogenetics – but also by the wide use of anthropological materials. Prior to these works, all information about the population of the Jochid ulus was fragmentary and unsystematic, and he was the very researcher who first connected the data of paleoanthropology and the analysis of the burial rite in medieval burial grounds. He proved the fact that the Golden Horde population consisted of mixed population groups, and identified those population groups that, in his opinion, came from Central Asia. L.T. Yablonsky attached great importance to the methodology of research on ethnogenesis and ethnic history. He advocated an integrated scientific approach to their study and emphasized the huge role of paleoanthropology and archaeology in solving ethnogenetic problems. In his opinion, the rapid divergence of various scientific disciplines – ethnology, archaeology, physical anthropology, and genetics – was the main problem that hindered the development of scientific ethnogenetic research. L.T. Yablonsky, therefore, believed that expanding comprehensive research would help solve this problem.